A c-di-GMP-Modulating Protein Regulates Swimming Motility of Burkholderia cenocepacia in Response to Arginine and Glutamate - Kumar, Brijesh; Sorensen, John L.; Cardona, Silvia T. (Frontiers in Cellular and Infection Microbiology, 2018)
Burkholderia cenocepacia is an opportunistic bacterium that can thrive in different environments, including the amino acid-rich mucus of the cystic fibrosis (CF) lung. B. cenocepacia responds to the nutritional conditions that mimic the CF sputum by increasing flagellin expression and swimming motility. Individual amino acids also induce swimming but not flagellin expression. Here, we show that modulation of the second messenger cyclic dimeric guanosine monophosphate (c-di-GMP) levels by the PAS-containing c-di-GMP phosphodiesterase, BCAL1069 (CdpA), regulates the swimming motility of B. cenocepacia K56-2 in response to CF sputum nutritional conditions. Heterologous expression of WspR, a diguanylate cyclase, in B. cenocepacia K56-2 caused an increase in c-di-GMP levels and reduced swimming motility but did not affect flagellin expression or flagellar biosynthesis. After insertional mutagenesis of twelve putative genes encoding c-di-GMP metabolizing enzymes, one mutant of the locus BCAL1069 (cdpA), exhibited decreased swimming motility independent of flagellin expression in CF sputum nutritional conditions and an increase in intracellular c-di-GMP levels. The reduced swimming motility phenotype of the BCAL1069 mutant was observed in the presence of arginine and glutamate, but not of histidine, phenylalanine or proline. The B. cenocepacia CdpA was also found to be involved in regulation of protease activity but not in biofilm formation. Altogether, these results highlight a role of B. cenocepacia BCAL1069 (CdpA) in sensing the nutritional conditions of the CF sputum and eliciting a pathogenic response that includes swimming motility towards amino acids and an increase in protease activity.